The Influence Of Selected Factors On ProfessionalnCommitment of Technical School Teachers In Sarawak - Chua, Lee Chuan (2004)
Although studies on commitment are prevalent in the education literature, most of these studies generally focused on commitment as a unidimensional concept. Recent studies provided evidence that commitment is multi-dimensional (Meyer and Allen, 1990, 1991, 1997), but received little attention from researchers. Acknowledging that commitment is multi-dimensional in nature, this study was undertaken to use a three-component commitment model, proposed by Meyer and Allen's (1990) to examine professional commitment. The study also examined the extent to which professional commitment can be predicted by perceived principal support, collegial support, role states and job characteristics. Data were collected from 120 randomly selected technical school teachers in Sarawak, using self-administered questionnaires. Overall, the study concluded that technical school teachers were highly committed to the teaching profession. They reported relatively high levels of affective, continuance and normative commitment. Results obtained from the correlation analysis revealed that teachers who perceived high levels of principal support, collegial support and job characteristics were more committed to the teaching profession. However, teachers who perceived high levels of role states were relatively less committed. Principal support, collegial support and job characteristics were also strongly related to affective, continuance and normative commitment. Role states were negatively related to affective commitment but positively related to continuance commitment. Results from a series of regression models revealed that overall professional commitment was predicted by principal support (emotional support), collegial support and job characteristics (feedback) but not role states. These three predictors explained 46.1% of the variance in professional commitment. Separately assessing each of the three components of professional commitment, it was found that affective, continuance and normative commitment were predicted by different clusters of factors. Specific results showed that affective commitment was highly dependent on emotional support, role conflict, skill variety, task significance and feedback. These predictors explained 38.3% of the variance in affective commitment. Only skill variety was significant in explaining continuance commitment, which contributed 1 1.7% of the variance in continuance commitment.Normative commitment closely resembled the pattern of results found in professional commitment, with emotional support, collegial support and feedback as significant predictors. These predictors explained 39.9% of the variance in normative commitment. The results of this study highlighted the importance of recognising that professional commitment be viewed as a multi-dimensional concept. Therefore, more studies should look into the multi-dimensional aspect of commitment to gain a more comprehensive understanding of the true nature of professional commitment. Based on the statistical results, implications of the findings were discussed in the context of understanding professional commitment of teachers. Suggestions on how to increase professional commitment and avenues for hture research were also provided in this dissertation.